2017
DOI: 10.1111/puar.12817
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Organizational Red Tape and Organizational Performance in Public Services

Abstract: The claim that perceived organizational red tape hampers public services has become a central theme in public administration research. Surprisingly, however, few scholars have empirically examined the impact of perceived red tape on organizational performance. This article empirically analyzes how perceived organizational red tape among managers and frontline staff relates to objectively measured performance. The data consist of survey responses from teachers and principals at Danish upper secondary schools co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 53 publications
(85 reference statements)
1
49
0
Order By: Relevance
“…Work units that are more burdened by the rules they face in their job are less able to produce a high level of output. In the current context, a healthcare service organization, this is likely to be due to constraints because of a lack of time (Jacobsen and Jakobsen ). A compliance burden simply takes time and resources away from work units; as opposed to doing their regular tasks such as showering clients, the employees are spending time filling in paperwork.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Work units that are more burdened by the rules they face in their job are less able to produce a high level of output. In the current context, a healthcare service organization, this is likely to be due to constraints because of a lack of time (Jacobsen and Jakobsen ). A compliance burden simply takes time and resources away from work units; as opposed to doing their regular tasks such as showering clients, the employees are spending time filling in paperwork.…”
Section: Discussionmentioning
confidence: 99%
“…The limited empirical studies on the relationship between red tape and performance have in general found negative effects (Pandey et al ; Walker and Brewer ; Jacobsen and Jakobsen ). In an overview of the findings, Brewer and Walker () conclude that evidence can be seen as inconclusive at most.…”
Section: The Relationship Between Red Tape and Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Organizational red tape refers to rules, regulations, and procedures that remain in force and entail a compliance burden for the organization but have no efficacy for the rules' functional object (Bozeman ). As Jacobsen and Jakobsen () indicated, the functionality of rules has a perceived aspect, and almost all published studies have measured red tape as a perceptual phenomenon. They defined perceived red tape as “the perception that rules and procedures (formalization) in an organization are detrimental to organizational performance” (Jacobsen and Jakobsen , 26).…”
Section: A Comprehensive Frameworkmentioning
confidence: 99%